Bacterial Diversity of a Microbial Mat from Hot Spring at Wartawan Beach, Lampung and Its Potential as a Source of Hydrogenases - Gintung Patantis; Ekowati Chasanah; Yusro Nuri Fawzya; He Pe Qing; Zhang Xue Lei (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Biohydrogen produced from thermophilic hydrogenases is an ideal and clean energy sources. As the biggest tectonic area in the world, Indonesia is potential for thermophile isolation. The aims of this study were to analyze the bacterial diversity of a microbial mat from hot spring at Wartawan beach, Lampung and to analyze the potency of microbial mat for hydrogenases, using clone library method. The diversity of 16S rRNA showed that the microbial mat sample contained 9 phyla of bacteria, and dominated by Cyanobacteria and Proteobacteria. These phyla indicate that the bacterial community of the microbial mat consisted of phototrophic and heterotrophic groups. In addition, a microbial mat of Wartawan beach environment might be influenced by marine environment and hydrothermal vent which was indicated by detection of both associated bacteria. The diversity of hydrogenase genes using NiFe hydrogenase (NiFe) and FeFe hydrogenase (FeFe) genes showed that Cyanobacteria was specifically related to NiFe, while Firmicutes was associated with FeFe. Proteobacteria and Bacteroidetes, however, were detected for both genes. The detected hydrogenase genes indicate that the microbial mat from hot spring at Wartawan beach is a promising source for hydrogenases isolation and further applications for biohydrogen production as a renewable energy.